(untitled) (Doctor Virtualis, 2023)
The history of medieval theology and metaphysics is marked by a relevant discussion about the predication of being. The semantic devices most frequently referred to in this regard were, as is well known, analogy and univocity. With respect to this alternative, the general tendency of scholars has been to understand univocity and analogy as opposite and contradictory modes of predication. This view has led to a kind of common and widely shared opinion. This thesis, however, has never prevailed conclusively: a debate on whether univocity and analogy were compatible dates back to the Middle Ages. In this respect, the contribution of Petrus Thomae (Pere Tomàs, Pietro Tomàs) is decisive: the seventh of his Quaestiones de ente (ca. 1325) asks in fact Utrum vera analogia et vera univocatio possint se compati in eodem conceptu. This contribution tries to reconstruct the main points of Petrus Thomae’s argumentation with the twofold purpose of enhancing the contribution of this author in the framework of the medieval theological debate and of justifying the opportunity of the current research that tries to rethink the relationship between univocity and analogy in the context of Duns Scotus’ thought.